Resistance to Bipyridyls Mediated by the TtgABC Efflux System in Pseudomonas putida KT2440 - Tania Henríquez; Nicola Victoria Stein; Heinrich Jung (Frontiers in Microbiology, 2020)
Resistance-nodulation-division (RND) transporters are involved in antibiotic resistance and have a broad substrate specificity. However, the physiological significance of these efflux pumps is not fully understood. Here, we have investigated the role of the RND system TtgABC in resistance to metal ion chelators in the soil bacterium Pseudomonas putida KT2440. We observed that the combined action of an RND inhibitor and the chelator 2,2'-bipyridyl inhibited bacterial growth. In addition, the deletion of ttgB made the strain susceptible to 2,2'-bipyridyl and natural bipyridyl derivatives such as caerulomycin A, indicating that TtgABC is required for detoxification of compounds of the bipyridyl family. Searching for the basis of growth inhibition by bipyridyls, we found reduced adenosine triphosphate (ATP) levels in the ttgB mutant compared to the wild type. Furthermore, the expression of genes related to iron acquisition and the synthesis of the siderophore pyoverdine were reduced in the mutant compared to the wild type. Investigating the possibility that 2,2'-bipyridyl in the ttgB mutant mediates iron accumulation in cells (which would cause the upregulation of genes involved in oxidative stress via the Fenton reaction), we measured the expression of genes coding for proteins involved in intracellular iron storage and the response to oxidative stress. However, none of the genes was significantly upregulated. In a further search for a possible link between 2,2'-bipyridyl and the observed phenotypes, we considered the possibility that the ion chelator limits the intracellular availability of metabolically important metal ions. In this context, we found that the addition of copper restores the growth of the ttgB mutant and the production of pyoverdine, suggesting a relationship between copper availability and iron acquisition. Taken together, the results suggest that detoxification of metal chelating compounds of the bipyridyl family produced by other bacteria or higher ordered organisms is one of the native functions of the RND efflux pump TtgABC. Without the efflux pump, these compounds may interfere with cell ion homeostasis with adverse effects on cell metabolism, including siderophore production. Finally, our results suggest that TtgABC is involved in resistance to bile salts and deoxycholate.